Social peferences under risk: experimental analysis - Christiane Bradler (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
The literature on social preferences provides overwhelming evidence of departures from pure self-interest of individuals. Experiments show that people care about others' well-being and their relative standing. This paper investigates whether this type of behavior persists when risk comes into play. I devise an experiment which sheds light on the interrelation of risk and social preferences by measuring (1) individual risk preferences, (2) interpersonal risk preferences, and (3) social preferences under certainty. The results reveal that a large share of subjects choose to accept more risk or less potential gain than individually preferred in order to increase another subject's payoff. Further, the willingness to do so appears to be influenced by the need of the other person and her potential relative standing. Surprisingly, the results do not suggest that a subject's social behavior under risk is related to his exhibited social concerns exhibited under certainty.
Keywords: D81; D63; C91; 330; Social preferences; risk; other-regarding behavior; inequality aversion; Soziale Wohlfahrtsfunktion; Entscheidung bei Unsicherheit; Risikopräferenz; Test